Question regarding the running times of f1(n) and f2(n) : https://gateoverflow.in/495/gate2008-74

The Gateway to Computer Science Excellence

+20 votes

Consider the following C functions:

int f1 (int n) { if(n == 0 || n == 1) return n; else return (2 * f1(n-1) + 3 * f1(n-2)); } int f2(int n) { int i; int X[N], Y[N], Z[N]; X[0] = Y[0] = Z[0] = 0; X[1] = 1; Y[1] = 2; Z[1] = 3; for(i = 2; i <= n; i++){ X[i] = Y[i-1] + Z[i-2]; Y[i] = 2 * X[i]; Z[i] = 3 * X[i]; } return X[n]; }

$f1(8)$ and $f2(8)$ return the values

- $1661$ and $1640$
- $59$ and $59$
- $1640$ and $1640$
- $1640$ and $1661$

+10 votes

Best answer

Both $f1$ and $f2$ are calculating the same function in recursive and iterative fashion respectively.

So. lets solve the recurrence relation.

$F(n) = 2 F(n-1) + 3F(n-2)$

Its characteristic equation will be

$r^{2}- 2r- 3 = 0$

$\implies (r-3) (r+1) = 0$

$\implies r = 3, -1$

Now, we have two roots. So the equation will be

$a_{n} = C_{1}(-1^{n}) + C_{2}(3^{n}) \qquad \to (1)$

Now from the function $f1,$

$F(0) = 0$ and $F(1) = 1$

So, $C_{1} + C_{2} = 0$

$\quad -C_{1} + 3C_{2} = 1$

$\implies C_{1} = -1/4$ and $C_{2} = 1/4$

After putting the values in $(i)$ the equation will become

$a_{n} = (-1/4)(-1^{n}) +(1/4)(3^{n})$

Putting $n= 8$ it will become

$F(8) = a_{8} = 1640.$

Or we can do it manually

$f1(2) = 2f1(1) + 3f1(0) = 2$

$f1(3) = 2f1(2) + 3f1(1) = 7$

$f1(4) = 20$

$f1(5) = 61$

$f1(6) = 182$

$f1(7) = 547$

$f1(8) = 1640 = f2(8)$

+16 votes

+6 votes

First, we'll see what $f1(8)$ will return

int f1(int n)

{

if(n == 0 || n == 1)

return n;

else

return(2*f1(n-1) + 3 * f1(n-2));

}

∴ $f1(8)$ returns $1640$

Now, what $f2(8) $ will return --

int i;

We can take any values of $i$, but at the end, we want the return value as $X[n]$, so we'll going to take $i=8$

int X[N], Y[N], Z[N];

The above line creates $3$ arrays

X[0] = Y[0] = Z[0] = 0;

This will set all the index $0$ position of all the $3$ arrays to $0$

X[1] = 1; Y[1] = 2; Z[1] = 3;

for(i=2; i<= n; i++)

This loop will run from $i=2$ to $i=8$

X[i] = Y[i-1] + Z[i-2]; Y[i] = 2 * X[i]; Z[i] = 3 * X[i];

when $i = 2$ ,

$X[ i ] = Y[ i-1 ] + Z[ i-2 ]$ $\rightarrow X[2] = Y[2-1] + Z[2-2] \\ = Y[1] + Z[0] = 2 + 0 \\ = 2$

$Y[i] = 2 * X[i]$ $\rightarrow Y[2] = 2 * X[2] \\ = 2 * 2 \\ = 4$

$Z[i] = 3 * X[i]$ $\rightarrow Z[2] = 3 * X[2] \\ = 3 * 2 \\ = 6$

when $i = 3$ ,

$X[ i ] = Y[ i-1 ] + Z[ i-2 ]$ $\rightarrow X[3] = Y[3-1] + Z[3-2] \\ = Y[2] + Z[1] = 4 + 3 \\ = 7$

$Y[i] = 2 * X[i]$ $\rightarrow Y[3] = 2 * X[3] \\ = 2 * 7 \\ = 14$

$Z[i] = 3 * X[i]$ $\rightarrow Z[3] = 3 * X[3] \\ = 3 * 7 \\ = 21$

when $i = 4$ ,

$X[ i ] = Y[ i-1 ] + Z[ i-2 ]$ $\rightarrow X[4] = Y[4-1] + Z[4-2] \\ = Y[3] + Z[2] = 14 + 6 \\ = 20$

$Y[i] = 2 * X[i]$ $\rightarrow Y[4] = 2 * X[4] \\ = 2 * 20 \\ = 40$

$Z[i] = 3 * X[i]$ $\rightarrow Z[4] = 3 * X[4] \\ = 3 * 20 \\ = 60$

when $i = 5$ ,

$X[ i ] = Y[ i-1 ] + Z[ i-2 ]$ $\rightarrow X[5] = Y[5-1] + Z[5-2] \\ = Y[4] + Z[3] = 40 + 21 \\ = 61$

$Y[i] = 2 * X[i]$ $\rightarrow Y[5] = 2 * X[5] \\ = 2 * 61 \\ = 122$

$Z[i] = 3 * X[i]$ $\rightarrow Z[5] = 3 * X[5] \\ = 3 * 61 \\ = 183$

when $i = 6$ ,

$X[ i ] = Y[ i-1 ] + Z[ i-2 ]$ $\rightarrow X[6] = Y[6-1] + Z[6-2] \\ = Y[5] + Z[4] = 122 + 60 \\ =182$

$Y[i] = 2 * X[i]$ $\rightarrow Y[6] = 2 * X[6] \\ = 2 * 182 \\ = 364$

$Z[i] = 3 * X[i]$ $\rightarrow Z[6] = 3 * X[6] \\ = 3 * 182 \\ = 546$

when $i = 7$ ,

$X[ i ] = Y[ i-1 ] + Z[ i-2 ]$ $\rightarrow X[7] = Y[7-1] + Z[7-2] \\ = Y[6] + Z[5] = 364 + 183 \\ = 547$

$Y[i] = 2 * X[i]$ $\rightarrow Y[7] = 2 * X[7] \\ = 2 * 547 \\ = 1094$

$Z[i] = 3 * X[i]$ $\rightarrow Z[7] = 3 * X[7] \\ = 3 * 547 \\ = 1641$

when $i = 8$ ,

$X[ i ] = Y[ i-1 ] + Z[ i-2 ]$ $\rightarrow X[8] = Y[8-1] + Z[8-2] \\ = Y[7] + Z[6] = 1094 + 546 \\ = 1640$

$Y[i] = 2 * X[i]$ $\rightarrow Y[8] = 2 * X[8] \\ = 2 * 1640 \\ = 3280$

$Z[i] = 3 * X[i]$ $\rightarrow Z[8] = 3 * X[8] \\ = 3 * 1640 \\ = 4920$

Now we'll be coming out from for loop & execute the last statement

return X[n];

which will return $X[n]$ i.e. $X[8]$ which is $1640$

∴ $f1(8)$ will return $1640$ & $f2(8)$ will also return $1640$

**The correct option will be C).**

+5 votes

Both functions are same. One is the recursive version and other is the itrative version. so find anyones's value is sufficient.

let's find value of f1(8).

f1(0)=0

f1(1)=1

f1(2)=2*f1(1) + 3*f1(0) = 2; likewise for others

f1(3)=4 + 3 = 7

f1(4)=14 + 6 = 20

f1(5)=40 + 21 = 61

f1(6)=122 + 60 = 182

f1(7)=364 + 183 = 547

f1(8)= 1094 + 546 = 1640

(C.) is the answer.

let's find value of f1(8).

f1(0)=0

f1(1)=1

f1(2)=2*f1(1) + 3*f1(0) = 2; likewise for others

f1(3)=4 + 3 = 7

f1(4)=14 + 6 = 20

f1(5)=40 + 21 = 61

f1(6)=122 + 60 = 182

f1(7)=364 + 183 = 547

f1(8)= 1094 + 546 = 1640

(C.) is the answer.

+2 votes

f1 and f2 are computing same function. f1 is Top Down method using recursion and f2 is Bottom Up method using DP.

This problem could be solved via forming recurrence relation. Solution of Homogenous recurrence relation is ->

a(n) = $\frac{1}{4}*(3^n - (-1)^n)$

a(8) = 1640.

Hence answer is C part.

This problem could be solved via forming recurrence relation. Solution of Homogenous recurrence relation is ->

a(n) = $\frac{1}{4}*(3^n - (-1)^n)$

a(8) = 1640.

Hence answer is C part.

- All categories
- General Aptitude 1.8k
- Engineering Mathematics 7.4k
- Digital Logic 2.9k
- Programming and DS 4.9k
- Algorithms 4.4k
- Theory of Computation 6.2k
- Compiler Design 2.1k
- Databases 4.1k
- CO and Architecture 3.4k
- Computer Networks 4.1k
- Non GATE 1.5k
- Others 1.7k
- Admissions 595
- Exam Queries 576
- Tier 1 Placement Questions 23
- Job Queries 72
- Projects 17

50,666 questions

56,138 answers

193,704 comments

93,489 users